Arvin Farm Labor Camp - Dorothea Lange:::Creator::::::::::::
A meeting of the 'Good Neighbors Society.' at the Arvin Farm Labor Camp known as Weedpatch. Women stand around a sewing machine, praying. Lange's photographs influenced the development of documentary photography and humanized the consequences of the Great Depression.